2013
DOI: 10.4236/fns.2013.42026
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Analysis of Morusin from <i>Ramulus mori</i> by HPLC-DAD, Its Distribution <i>in Vivo</i> and Differentiation in the Cultivated Mulberry Species

Abstract: The distribution and content differentiation of morusin in the cultivated species of mulberry by HPLC-DAD are described in this paper. The experimental results showed that morusin is present in all parts of the mulberry bush. The content of morusin was highest in root bark and second highest in branch bark. The difference in morusin content of 20 different species of cultivated mulberry branch bark was significant. The level of morusin was highest in the branch bark of cultivated mulberry No. 404, a tetraploid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In our laboratory, we studied the extraction of active components such as polysaccharides [20, 21], 1-deoxynojirimycin [22], mulberroside A [19], and morusin [23] from mulberry branch bark. The results showed that the extract of mulberry branch bark has bioactivities of antioxidation [19], hypoglycaemia [24], hypolipidemia, and anticancer [25].…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, we studied the extraction of active components such as polysaccharides [20, 21], 1-deoxynojirimycin [22], mulberroside A [19], and morusin [23] from mulberry branch bark. The results showed that the extract of mulberry branch bark has bioactivities of antioxidation [19], hypoglycaemia [24], hypolipidemia, and anticancer [25].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin ( (Tao et al, 2013), quercetin-3-O-α-L-rhamnopyranosyl-(1→6)-β-D-glucopyranoside (rutin) (23), quercetin 3-(6-malonylglucoside) (Q3MG) (24) (Katsube et al, 2010), quercetin3-(6acetylglucoside) (Q3AG) (25), kaempferol3-(6-rhamnosylglucoside) (K3RG) (26), kaempferol3-(6malonylglucoside) (K3MG) (27) (Sugiyama et al, 2013), morusin (28) (Ma et al, 2013), sanggenon C (29), sanggenon G (30), kuwanon L (31) (Cui et al, 2006) (Figure 3).…”
Section: Flavonoidsmentioning
confidence: 99%
“…Morusin (28) is an isoprenylated flavone, isolated from the root bark of M. alba; its structure has been identified (Figure 3) (Chi et al, 2001). It has been showed that morusin is present in all parts of the mulberry plant (Ma et al, 2013). The content of morusin is highest in root bark and second highest in branch bark.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Our group had investigated in details the difference of morusin in 100 kinds of mulberry branch bark by RP-HPLC-DAD (reverse-phase high-performance liquid chromatography) with diode array detector, and the maximum amount was found to be 585.81 µg/g and 20 times to the minimum [ 22] . Similarly, morusin was found to restrain the proliferation of human hepatocarcinoma Bel-7402 cells, resulting in a survival rate of tumour cells of only 34.56% and an apoptotic rate of cancer cells reaching 81% in high concentrations with a dose-dependent manner [ 23] .…”
Section: Introductionmentioning
confidence: 99%